Unsymmetrical α-diimine palladium catalysts and their properties in olefin (co)polymerization. (14th December 2016) - Sui, Xuelin; Hong, Changwen; Pang, Wenmin; Chen, Changle
Abstract : Interconvertible rac and meso forms of α-diimine ligands. Nickel catalysts led to the formation of bimodal polyethylene. Palladium catalysts led to the formation of unimodal polymers. The tunable mechanical and surface properties of polyolefin. Abstract : Previously, it was demonstrated that nickel complexes bearing unsymmetrical α-diimine ligands generated polymers with a broad molecular weight distribution in ethylene polymerization. In this contribution, the influence of some unsymmetrical α-diimine ligands on the catalytic properties of their palladium complexes was investigated in ethylene polymerization, ethylene–methyl acrylate copolymerization and 1-hexene polymerization. Quite interestingly, the unsymmetrical α-diimine ligand structures did not lead to a broad molecular weight distribution in these polymerization and copolymerization reactions. In addition, the influence of different substituents (OMe, Me, Cl and NO2 ) and different backbone structures was studied. The palladium complexes bearing electron-donating groups showed higher thermal stability and afforded polymers with a much higher molecular weight. The palladium complex bearing naphthalene backbone showed a much lower catalytic activity, generating polymers or copolymers with a much lower molecular weight. The mechanical and surface properties of the resulting polymer and copolymer were also investigated.